On the physical nature of globular cluster candidates in the Milky Way bulge - Piatti, Andres Eduardo (2018)
We present results from 2MASS JKs photometry on the physical reality of recently reported globular cluster (GC) candidates in the Milky Way (MW) bulge. We relied our analysis on photometric membership probabilities that allowed us to distinguish real stellar aggregates from the composite field star population. When building colour-magnitude diagrams and stellar density maps for stars at different membership probability levels, the genuine GC candidate populations are clearly highlighted. We then used the tip of the red giant branch (RGB) as distance estimator, resulting in heliocentric distances that place many of the objects in regions near the MW bulge, where no GC had been previously recognized. Some few GC candidates resulted to be MW halo/disc objects. Metallicities estimated from the standard RGB method are in agreement with the values expected according to the position of the GC candidates in the Galaxy. Finally, we derived, for the first time, their structural parameters. We found that the studied objects have core, half-light, and tidal radii in the ranges spanned by the population of known MW GCs. Their internal dynamical evolutionary stages will be described properly when their masses are estimated.